2005
DOI: 10.1371/journal.pmed.0020089
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thyroid Disease with Fluctuating Thyroid Function

Abstract: The authors describe the case of a woman with autoimmune thyroid disease, who presented with hypothyroidism but went on to develop hyperthyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The histopathological studies obtained from the patients files revealed that 30 cases out of the 38 case with solitary nodules were benign As regarding thyroid cancer , patients with thyroid cancer in the current study were mainly males (75%) with papillary type of cancer (64.3% ) and the common presenting manifestation was hyperthyroidism (53.6%). (tables 7,8,9 ) The most common manifestation in Patients complaining of hypothyroidism in the present work was obesity (65.3%). Whereas it was palpitation in case of hyperthyroidism (87.7%) Table (10,11) Risk factors of thyroid disease include: Gender, Diet rich in goitrogens or deficient in iodine , Pregnancy , Radiation to the neck , Family history and Smoking (Marita et al , 2008 ) Hypothyroidism results from deficient production of the thyroid hormone or defects in thyroid hormone receptor activity.…”
Section: Results:-supporting
confidence: 49%
“…The histopathological studies obtained from the patients files revealed that 30 cases out of the 38 case with solitary nodules were benign As regarding thyroid cancer , patients with thyroid cancer in the current study were mainly males (75%) with papillary type of cancer (64.3% ) and the common presenting manifestation was hyperthyroidism (53.6%). (tables 7,8,9 ) The most common manifestation in Patients complaining of hypothyroidism in the present work was obesity (65.3%). Whereas it was palpitation in case of hyperthyroidism (87.7%) Table (10,11) Risk factors of thyroid disease include: Gender, Diet rich in goitrogens or deficient in iodine , Pregnancy , Radiation to the neck , Family history and Smoking (Marita et al , 2008 ) Hypothyroidism results from deficient production of the thyroid hormone or defects in thyroid hormone receptor activity.…”
Section: Results:-supporting
confidence: 49%
“…This is not the first case reported with fluctuating thyroid function (4). Antagonistic stimulatory and inhibitory TSH receptor antibodies in thyroid function cycling have been described (7).…”
mentioning
confidence: 70%
“…Rarely, patients may have recurrent fluctuations in thyroid function (4). Moreover, alternating trajectories of thyroid function may further puzzle practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…In two other cases, hypothyroidism was followed by persistent hyperthyroidism, and in one case hypothyroidism was associated with thyroid-stimulating antibodies, a characteristic finding in Graves's disease. Alzahrani describes Grave's disease after many years of hypothyroidism followed by a similar period of euthyroidism in a female [4].…”
Section: Test Parametermentioning
confidence: 99%